Enterokinase Enhances Influenza A Virus Infection by Activating Trypsinogen in Human Cell Lines - Hayashi, Hideki; Kubo, Yoshinao; Izumida, Mai; Takahashi, Etsuhisa; Kido, Hiroshi; Sato, Ko; Yamaya, Mutsuo; Nishimura, Hidekazu; Nakayama, Kou; Matsuyama, Toshifumi (Frontiers in Cellular and Infection Microbiology, 2018)
Cleavage and activation of hemagglutinin (HA) by trypsin-like proteases in influenza A virus (IAV) are essential prerequisites for its successful infection and spread. In host cells, some transmembrane serine proteases such as TMPRSS2, TMPRSS4 and HAT, along with plasmin in the bloodstream, have been reported to cleave the HA precursor (HA0) molecule into its active forms, HA1 and HA2. Some trypsinogens can also enhance IAV proliferation in some cell types (e.g., rat cardiomyoblasts). However, the precise activation mechanism for this process is unclear, because the expression level of the physiological activator of the trypsinogens, the TMPRSS15 enterokinase, is expected to be very low in such cells, with the exception of duodenal cells. Here, we show that at least two variant enterokinases are expressed in various human cell lines, including A549 lung-derived cells. The exogenous expression of these enterokinases was able to enhance the proliferation of IAV in 293T human kidney cells, but the proliferation was reduced by knocking down the endogenous enterokinase in A549 cells. The enterokinase was able to enhance HA processing in the cells, which activated trypsinogen in vitro and in the IAV-infected cells also. Therefore, we conclude that enterokinase plays a role in IAV infection and proliferation by activating trypsinogen to process viral HA in human cell lines.